Using geography information system in docmentation the electrcity netowk practice example Deir atya city( - Eid, Safieh; Ali, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of research is appear useful of geographic information system in electricity network. The research building the electricity of Dair Atya city with create database for each element of the network .that GIS helping to archive all electricity plans by link with real location in the ground and build database for all elements in the network (Substation, meter,…) and management the network with obtain the data and maps analysis to adjust the network to be able have good decision in future.